Peningkatan Hasil Belajar Bahasa Indonesia melalui Penerapan Strategi Pembelajaran Inkuiri (SPI) Siswa Kelas IV SDN 001 Koto Taluk Kuantan - Elniyeti, Elniyeti; Yuslianti, Yuslianti (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
The application of learning methods in each learning will have an impact on learning outcomes and the atmosphere of classroom learning and student activities in learning. One method that can be used is Inquiry Learning Strategies (SPI). This method is used in Classroom Action Research (PTK) Indonesian language learning material Exploring Information from Class IV Adventist Texts of Students in SD Negeri 001 Koto Taluk Kuantan. This study aims to get an idea of ​​how to improve student learning outcomes after using Inquiry Learning Strategies (SPI) methods in Indonesian language material. Exploring Information from the Class IV Adventurer's Texts in SD Negeri 001 Koto Taluk Kuantan. The study uses four steps of PTK, namely planning, action, observation, and reflection. The four components of the research step constitute one cycle. This research was carried out in two cycles. Improved student learning outcomes, in the initial data with an average of 67.1 increased in Deuteronomy Daily I to 75.2 with an increase of 12.1. In Deuteronomy Daily II it increased to 81.9 with an increase of 8.9. Then from individual and classical completeness, in the first cycle the total number of students completed was 10 people at 47.6% and the incomplete 11 people amounted to 52.4%, whereas in the second cycle the number of students who completed 19 people was 90.5%, , while the incomplete 2 people amounted to 9.5%. Thus, it can be concluded that Inquiry Learning Strategies (SPI) can improve the results of Indonesian language learning material Exploring Information from the Class IV Adventist Texts of Students in SD Negeri 001 Koto Taluk Kuantan.